A Version of Uncertainty Principle for Quaternion Linear Canonical Transform - Mawardi Bahri; Resnawati; Selvy Musdalifah (Abstract and Applied Analysis)
In recent years, the two-dimensional (2D) quaternion Fourier and quaternion linear canonical transforms have been the focus of many research papers. In the present paper, based on the relationship between the quaternion Fourier transform (QFT) and the quaternion linear canonical transform (QLCT), we derive a version of the uncertainty principle associated with the QLCT. We also discuss the generalization of the Hausdorff-Young inequality in the QLCT domain.